The Moluccas' Surviving Aristocracy in Indonesian Politics - B. D. Kurniadi (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
The article demonstrates how the Sultanate of Ternate in the Moluccas has survived in post-authoritarian Indonesian politics by analysing the political performances of the Sultan of Ternate and his immediate family members. The success of Sultan Mudaffar Syah in the political arena has contextualised the literature on land-based political economy, something that has largely been neglected. Combining in-depth interviews, observations, and document study, I argue that the Sultan's political achievements were the result of his transforming Ternate's coastal aristocracy into a land-based one, sidestepping the Basic Agrarian Law (BAL) of 1960 by transferring land management and ownership to indigenous communities while still maintaining economic control. However, his wife and children have failed politically, not only because they are not part of the traditional aristocratic structure (and thus have no control over land) but also because of internal fragmentation.